Maternity Behavior and Infant Care of Coastal Communities on the Prevention of Neonatal Mortality: Prevention of Neonatal Mortality - Yunita Amraeni; La Ode Saafi; Azis Harun (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Infant mortality is one of the targets of health problems in sustainable development. The vast majority of infant deaths are preventable, with high-quality, evidence-based interventions in the form of data. Based on the results of the Indonesian Demographic and Health Survey (SDKI) infant mortality in 2017 was 24/1,000 KH with neonatal mortality of 15/1,000. There was a decrease in the infant mortality rate (IMR) in 2017, compared to the IMR in 2012 which amounted to 32/1,000 KH and 19/1,000 KH neonatal. This study aims to analyze the behavior of childbirth and infant care through the behavior of local wisdom so as to prevent neonatal death. Methods: This study uses a quantitative observational method through a Case Control Study Design approach. The population in this study were all mothers in the coastal area of the Konawe Islands Regency. Results: Birth behavior and baby care at risk provide opportunities for neonatal events. Health agencies need to increase education to the public about risk factors, causes of neonatal death and efforts to prevent neonatal death to mothers and expectant mothers and their families to pay attention to pregnant and postpartum women. Conclusion: For the community, it is necessary to regulate the age of marriage with efforts to control it from the local government